2018
DOI: 10.1016/j.ajme.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and six single nucleotide polymorphisms of interleukin-6 in rheumatoid arthritis: A case-control study in Iraqi patients

Abstract: Background: Interleukin-6 (IL-6) plays a significant role in pathogenesis of rheumatoid arthritis (RA), but its single nucleotide polymorphisms (SNPs), as well as therapy may modulate such role. Objectives: It was aimed to determine gene expression and six SNPs (rs1800796 C/G, rs7802307 A/C/T, rs7802308 A/T, rs36215814 A/G, rs184229712 A/G and rs867254801 C/G) of IL6 in etanercept-treated Iraqi Arab RA patients. Materials and methods: Fifty-one RA patients and 45 controls were enrolled, and the determinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
(36 reference statements)
2
10
0
Order By: Relevance
“…The isolated DNA was subjected to PCR amplification using designed forward (5′-GGTGAGAAAC CCTGCTATAAA-3′) and reverse (5′-CAAACATCTG CTCCTCCTC-3′) primers, which were employed to amplify intron 2 region of human chromosome X containing rs179018, rs179019, rs179020, and rs179021 SNPs (chrX:12866832+12867830). The PCR protocol and conditions were as previously described [12]. The amplified PCR fragments were subjected to Sanger's sequencing using ABI3730XL automated DNA sequencer (Macrogen Corporation-Korea).…”
Section: Tlr7 Gene Snpsmentioning
confidence: 99%
“…The isolated DNA was subjected to PCR amplification using designed forward (5′-GGTGAGAAAC CCTGCTATAAA-3′) and reverse (5′-CAAACATCTG CTCCTCCTC-3′) primers, which were employed to amplify intron 2 region of human chromosome X containing rs179018, rs179019, rs179020, and rs179021 SNPs (chrX:12866832+12867830). The PCR protocol and conditions were as previously described [12]. The amplified PCR fragments were subjected to Sanger's sequencing using ABI3730XL automated DNA sequencer (Macrogen Corporation-Korea).…”
Section: Tlr7 Gene Snpsmentioning
confidence: 99%
“…IL-6 and IL-8 were reported to be incriminated in the initiation and progression of prostate tumorigenesis, as IL-6 induces C-reactive protein (CRP) production [12]; promotes PCa cell survival, proliferation, invasion; enhances the progression of PCa to the castration-resistant state; and ® : reference group, OR: odds ratio, CI: confidence interval, UL: upper limit, LL: lower limit. OR 1 , p 1 : odds ratio and p value for comparing between cancer and control.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have examined the effect of IL-6 SNP and/or IL-8 SNP on diseases' risk, activity, and progression. Results showed marked ethnicity-associated disparities and diverse findings [12,[16][17][18][19][20][21][22][23]. For instance, a meta-analysis of European and Asian studies on IL-6 SNP and rheumatoid arthritis (RA) risk showed that IL-6 SNP was significantly associated with RA in Asian patients but not in the Caucasian population [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations